Analysis and forecast of the sea-ice in the Antarctic Peninsula - Tymofeev, V. Y. (Ukrainian Antarctic Journal, 2013)
The long-term change in the sea ice in the Antarctic shows growing in most months of the year, with a peak in March-May - a transition season with the formation of the seasonal ice. During the summer season a long-term retreat in the sea ice is found in water areas west of the Antarctic Peninsula on the background of significant inter-annual variations. Anomaly in the sea-ice cover is accompanied by an anomaly in the air and sea surface temperature (SST) fields and is caused by a certain type of atmospheric circulation. Advance of sea-ice during the summer seasons is observed against negative air temperature anomaly and the southern component of the wind. The study allows us to find the potential predictability of seasonal anomalies in the sea-ice. As predictors we used El Nіño index, indexes of regional atmospheric circulation, air temperature and SST measured at Vernadsky Station. To assess the development of the sea-ice anomalies it is necessary to identify the commencement of the spring retreat of the ice associated with the transition of the SST the freezing point. The consistency of the sea ice anomalies is important prognostic indicator in the seasonal time scale. Sea ice anomaly during the summer season 2011-2012 is analyzed in detail, when the planned shift of seasonal teams at Vernadsky Station was interrupted for the first time in many years. Type of atmospheric circulation responsible for the anomalous sea-ice is shown.